RECONSIDERING HABERMAS'S COLONIZATION THESIS a critical theory of neoliberalism. - Condon, Roderick (Routledge studies in social and political thought., 2025)
This book reconsiders Habermas's critique of capitalism as a foundation for a critical theory of neoliberalism. Taking criticisms into account, the author refines and redevelops Habermas's system-lifeworld paradigm in three parts, focusing on system, lifeworld, and communication. The exposition unfolds through a new synthesis and convergence, from within Habermas's frame, of Axel Honneth, Niklas Luhmann, Talcott Parsons, and Karl Marx. This synthesis is interwoven with an account of the neoliberal turn, such that social theory is historically contextualized and neoliberalism theoretically explained at one and the same time. The end result is a reconstruction of the colonization thesis in a new theory of relinguistification, advancing a communicative, dialectical, and reflexive theory of reification.Reconsidering Habermas's Colonization Thesis will appeal to scholars of critical theory, social theory, sociology, and cultural studies, as well as readers interested in neoliberalism and the critique of capitalism.